Pengaruh Sistem Penghargaan Berbasis Tim Terhadap Kolaborasi Dan Inovasi Di Tempat Kerja - Anwar, Ravel; Hadi, Rachman; Fitrasari, Raisa Dea; Amaliyah, Zakiyatul (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This study rigorously investigates how implementing team-based reward systems affects workplace collaboration and innovation. By employing a robust case study approach and a synthesis analysis of articles published between 2018 and 2023, this research provides compelling evidence that team-based rewards are a potent incentive, motivating team members to collaborate and achieve desired outcomes. This approach also effectively mitigates internal competition, which can impede the flow of information and knowledge sharing. The findings underscore that reward structures centered on collaboration bolster innovation and cultivate a more inclusive and productive work culture. Integrating financial and non-financial rewards, transparent and structured recognition, and transparency in performance evaluations has elevated employee motivation, performance, and loyalty. The study further emphasizes tailoring rewards to individual employee values and goals to enhance job satisfaction and organizational commitment. Moreover, transparency in the performance evaluation and reward distribution processes is pivotal for augmenting productivity and fairness in the workplace. The recommendations advocate for integrating team-based reward strategies as a fundamental component of human resource management policies. This study's implications suggest comprehensive and equitable reward strategies can enhance individual, team, and organizational performance. This study's reliability in the human resource management literature lies in exploring reward strategies for fostering collaboration and innovation within organizations.